2018
DOI: 10.1007/s11307-018-1195-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Labeling and Kit Preparation Method for Ga-68 Labeled DOTATATE, Using Cation Exchange Resin Purified Ga-68 Eluates Obtained from a Tin Dioxide 68Ge/68Ga Generator

Abstract: A labeling method using SCX-processed Ga-68 eluates was optimized. DOTATATE kits specifically for these SCX-processed Ga-68 eluates were successfully formulated. A post-labeling Sep-Pak C18 purification should be optional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the past few years, 68 Ge/ 68 Ga generators have increasingly played an important role in nuclear medicine clinics. , It is known that 68 Ga generator-based PET imaging agents have several unique advantages: (a) Germanium-68 ( 68 Ge) ( t 1/2 , 271 days), a long-lived isotope, facilitates a widespread generator circulation; (b) physical properties of 68 Ga ( t 1/2 , 68 min; 89% β + ; 1.92 MeV max energy) are appropriate for PET imaging; (c) 68 Ge/ 68 Ga generators provide an easy distribution for obtaining a positron-emitting isotope without the need of a nearby cyclotron. , For radionuclide therapy, decay characteristics of 177 Lu ( t 1/2 = 6.71 days, β – (max) = 497 keV) are very attractive and they have been successfully applied in treatment of different cancers. Recently, Lu-177 DOTATATE (Lutathera) was approved by the FDA for the treatment of gastroenteropancreatic neuroendocrine tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, 68 Ge/ 68 Ga generators have increasingly played an important role in nuclear medicine clinics. , It is known that 68 Ga generator-based PET imaging agents have several unique advantages: (a) Germanium-68 ( 68 Ge) ( t 1/2 , 271 days), a long-lived isotope, facilitates a widespread generator circulation; (b) physical properties of 68 Ga ( t 1/2 , 68 min; 89% β + ; 1.92 MeV max energy) are appropriate for PET imaging; (c) 68 Ge/ 68 Ga generators provide an easy distribution for obtaining a positron-emitting isotope without the need of a nearby cyclotron. , For radionuclide therapy, decay characteristics of 177 Lu ( t 1/2 = 6.71 days, β – (max) = 497 keV) are very attractive and they have been successfully applied in treatment of different cancers. Recently, Lu-177 DOTATATE (Lutathera) was approved by the FDA for the treatment of gastroenteropancreatic neuroendocrine tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Another PSMA kit, THP-PSMA by Rotop, contains 40 µg THP-PSMA, sodium bicarbonate, mannitol and phosphate buffer (Derlin et al 2018 ). An example of translating a manual labeling process to a kit preparation is outlined in Prince et al, who reported the optimization of [ 68 Ga]Ga-DOTA-TATE kit formulation (Prince et al 2018 ).…”
Section: Ga Radiopharmaceutical Production Techniquesmentioning
confidence: 99%
“…Therefore, there has been a strong focus on the development of novel tracer molecules with faster kinetics that allow an earlier imaging timepoint, reducing the radiation dose to healthy tissues and improving the overall imaging contrast. Antibody fragments [ 4 ], scaffold proteins [ 5 ], and peptides [ 6 ] have all been shown to be capable of this.…”
Section: Introductionmentioning
confidence: 99%